Efectividad de la noradrenalina vs etilefrina en la hipotensión materna posterior a anestesia raquídea en cesareada anterior en el Hospital Regional de Loreto 2024 - Guevara Marin, Jhonatan Martin (2025)
Project title: "Effectiveness of noradrenaline vs etilefrine in maternal hypotension after spinal anesthesia in anterior cesarean section in the Regional Hospital of Loreto 2024". General objective: To compare the effectiveness of noradrenaline versus etilefrine in the treatment of maternal hypotension after spinal anesthesia in patients undergoing anterior cesarean section at the Regional Hospital of Loreto 2024. Methodology: analytical, longitudinal, observational prospective cohort study. Research design: Prospective cohort study where variables are manipulated, where the dependent variable is the effectiveness, the return of MAP after hypotension caused by the placement of spinal anesthesia for cesarean section, and the independent variable, will depend on the vasopressor used, according to the recommendations of current protocols. Population and sample: Pregnant women who underwent cesarean section at the Regional Hospital of Loreto from January to July 2024. Data collection techniques and instruments: A data collection form will be used with the results of the application of two vasopressors with respect to the hemodynamic assessment of the patient during the intraoperative period. Data processing: Frequency distribution analysis will be performed for qualitative variables and the Z test for proportions will be used. Protection of human rights: The study will require the research and ethics authorization of the Regional Hospital of Loreto and the National University of the Peruvian Amazon, since it is a prospective cohort study in which no variables will be manipulated, informed consent will not be required.